Fire rather than nitrogen addition affects understory plant communities in the short term in a coniferous‐broadleaf mixed forest. Issue 16 (22nd July 2018) - Hu, Mengjun; Liu, Yanchun; Sun, Zhaolin; Zhang, Kesheng; Liu, Yinzhan; Miao, Renhui; Wan, Shiqiang
Abstract: Increasing fire risk and atmospheric nitrogen (N) deposition have the potential to alter plant community structure and composition, with consequent impacts on biodiversity and ecosystem functioning. This study was conducted to examine short‐term responses of understory plant community to burning and N addition in a coniferous‐broadleaved mixed forest of the subtropical‐temperate transition zone in Central China. The experiment used a pair‐nested design, with four treatments (control, burning, N addition, and burning plus N addition) and five replicates. Species richness, cover, and density of woody and herbaceous plants were monitored for 3 years after a low‐severity fire in the spring of 2014. Burning, but not N addition, significantly stimulated the cover (+15.2%, absolute change) and density (+62.8%) of woody species as well as herb richness (+1.2 species/m 2, absolute change), cover (+25.5%, absolute change), and density (+602.4%) across the seven sampling dates from June 2014 to October 2016. Light availability, soil temperature, and prefire community composition could be primarily responsible for the understory community recovery after the low‐severity fire. The observations suggest that light availability and soil temperature are more important than nutrients in structuring understory plant community in the mixed forest of the subtropical‐temperate transition zone in Central China. Legacy woody and herb species dominated the understory vegetation over the 3 years after fire, indicating strong resistance and resilience of forest understory plant community and biodiversity to abrupt environmental perturbation. Abstract : The positive effects of fire but no effects of N addition or its interaction with burning on the understory communities suggest that both light resource and soil temperature rather than nutrient resource dominate in regulating understory plant community. The study highlights that abrupt environment perturbations (fire) are more important than chronical environment perturbation (atmospheric N deposition) in structuring forest understory plant community in the short term.